Tinjauan Yuridis Beban Pembuktian Terbalik Pada Tindak Pidana Pencucian Uang - Saraswati, Anggittyas Ajeng; , Sudaryono, S.H, M.Hum; , Muchamad Iksan, SH, M.H (2015)
This research was conducted with the aim of knowing the problems of juridical possibility of the implementation of the system of proof is limited in combating money laundering and to identify conflicting or absence of proof system is limited by the presumption of innocence. This research method is a kind of normative legal research. Sources of data obtained from secondary data source of primary law, secondary and tertiary. Data were collected through library research. The data analysis technique used is qualitative data analysis with inductive method. Based on the results of this study concluded that, there are some problems of jurisdiction arising from the implementation of the system of proof on money laundering, the burden of proof imposed on the accused is limited to the trial phase and is limited to proving the origin of the assets only, so that the verification system is not violating Human Rights.